ANALISIS PENGARUH KUALITAS PRODUK DAN BAURAN PROMOSI TERHADAP LOYALITAS KONSUMEN SMARTPHONE BLACKBERRY (Studi pada Mahasiswa di Beberapa Universitas di Jakarta) - Dewi Nur Permatasari (MIX: JURNAL ILMIAH MANAJEMEN, 2014)
Abstract: This research aims to determine and analyze the influence of product quality and promotional mix on customer’s loyalty. The population in this study were all BlackBerry customers from student level in five university in Jakarta. The concept of product quality and promotion mix were adopted from various sources, both primary and secondary data is obtained. Determination of the sample in this research is non propability stratified sampling method. Validity and reliability are used to measure each variable item of research. Furthermore, multiple linear regression analysis, t test, f test, and then correlation analysis used the SPSS program. Based on the result of the regression analysis, it was found that the product quality variable and promotion mix variable influence significantly partially on customer’s loyalty. Similarly product quality variable and promotional mix variable simultaneously gives significant effect on customer’s loyalty.Keywords: product quality, promotional mix, customer’s loyalty